Digitalization for family documents: Improving awareness of digital archives using Google Drive for facing industry 4.0 - Febrika Yogie Hermanto; Meylia Elizabeth Ranu; Triesninda Pahlevi; Jaka Nugraha; Berlina Hidayati; Anthony Ogbolu Nnamdi; Maratus Sholikah (Journal of Community Service and Empowerment, 2024)
It is necessary to understand digital-based family document management through training activities provided to the women's community in Sukodono-Sidoarjo. The aim of this program is to increase awareness of digital-based family document management in the era of technology 4.0 by providing lectures and practice of digital family archiving using Google Drive to mothers who have direct contact with managing documents in the family. This Community Service adopts experimental research with a quasi-experiment model, one group pretest-posttest design, where the level of success of the program can be seen from the increase in the training participants' abilities as shown by the results of the N-Gain Test calculation through Pretest and Posttest, affective scores, and psychomotor scores each participant. The results show that the digital-based family document management training agenda using Google Drive was effectively implemented by all participants based on the cognitive, affective and psychomotor aspects of this training. The effectiveness of this training has implications for increasing public awareness of digital archives for family documents owned by all participants, where this awareness is aimed at the use of digital public services in Sidoarjo. The use of the digital public service agenda promoted by the Government is an effort to increase SDGS 9 achievements in the indicator of the proportion of the population served by mobile broadband. Thus, the better prepared the community is to support digital public services, the higher the SDGs 9 score in a region/region.